2017
DOI: 10.1136/bmjopen-2016-014632
|View full text |Cite
|
Sign up to set email alerts
|

Productivity loss due to overweight and obesity: a systematic review of indirect costs

Abstract: ObjectiveThe increasingly high levels of overweight and obesity among the workforce are accompanied by a hidden cost burden due to losses in productivity. This study reviews the extent of indirect cost of overweight and obesity.MethodsA systematic search was conducted in eight electronic databases (PubMed, Cochrane Library, Web of Science Core Collection, PsychInfo, Cinahl, EconLit and ClinicalTrial.gov). Additional studies were added from reference lists of original studies and reviews. Studies were eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(176 citation statements)
references
References 75 publications
6
136
0
9
Order By: Relevance
“…It increases the risk for multiple chronic conditions, such as cardiovascular disease [1,2], diabetes mellitus [1], different kinds of cancers [3], some musculoskeletal disorders [4], and poor mental health [5]. Also, studies show that obesity can have negative influences on the quality of life, healthcare costs and work productivity [6,7]. The World Health Organization (WHO) has estimated that obesity affects 500 million people worldwide and it could potentially increase to one billion people globally by 2030 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It increases the risk for multiple chronic conditions, such as cardiovascular disease [1,2], diabetes mellitus [1], different kinds of cancers [3], some musculoskeletal disorders [4], and poor mental health [5]. Also, studies show that obesity can have negative influences on the quality of life, healthcare costs and work productivity [6,7]. The World Health Organization (WHO) has estimated that obesity affects 500 million people worldwide and it could potentially increase to one billion people globally by 2030 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is a factor that gradually increases direct and indirect healthcare costs and decreases productivity [9]. Andrea et al performed a systematic review of 50 studies on indirect costs of overweight and obesity and found that indirect costs were increased among overweight workers, and the costs were even higher among workers with obesity due to decreased productivity [10]. In modern society, the prevalence of overweight and obesity is steadily increasing due to the automation in jobs and an increase in unhealthy behaviors, such as the lack of physical activity, smoking, drinking, and unbalanced nutritional intake.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSÃO la que o nível de desemprego está positivamente associado ao quantitativo de cirurgias bariátricas realizadas em âmbito populacional via rede pública de saúde do Brasil 35 . Por outro lado, estudos também revelam que populações obesas tendem a apresentar menores índices de produtividade no trabalho 39,40 . Logo, combater a obesidade coletiva com métodos eficientes de tratamentos ofertados pelo sistema de saúde pública podem promover reduções significativas no custo associado a outras morbidades e promover aumento no desempenho produtivo dos indivíduos.…”
Section: Modalidadeunclassified